Gas chromatography–mass spectrometry analysis of nine bisphenols in canned meat products and human risk estimation. (September 2020) - Cunha, S.C.; Inácio, T.; Almada, M.; Ferreira, R.; Fernandes, J.O.
Graphical abstract: Highlights: GC–MS method showed to be reliable to determine BPA and eight analogues. BPA and their analogues in canned meat were determined. Canned meat meals revealed the highest percentage of bisphenols. Canned meat consumption can result in high hazard risk for human consumers. Abstract: The presence of bisphenol A (BPA) and eight BPA analogues was investigated in 30 canned meat samples (sausages, pâtés, and whole meals). For that, a previously developed gas chromatography-mass spectrometry (GC–MS) methodology based on a quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction followed by dispersive liquid–liquid microextraction (DLLME) with " in situ " acetylation was optimized, namely by the introduction of a novel solid-phase dispersive sorbent. Results showed that all the samples were contaminated with at least one compound from the five bisphenol analogues found (BPA, BPB, BPF, BPAF, and BPZ). Nineteen samples showed the simultaneous presence of BPA and one or more analogues, with a maximum of four different compounds in two of the samples. In half of the samples, the sum of all bisphenols was higher than 50 µg/kg, with a maximum of 236 µg/kg. Regarding human food safety, the estimated daily intake (EDI), target hazard quotient (THQ) and hazard index (HI) assessed were higher than those established by the European Food Safety Authority suggesting hazard risk for human consumers.